Characteristics of antibiotic production in a multiphase system - Elibol, Murat; Mavituna, Ferda (My University, 1997)
The production of an extracellular antibiotic, actinorhodin, was investigated in a 2-litre bench-top bioreactor. In order to determine the behaviour of Streptomyces coelicolor cells in a two liquids system, a perfluorocarbon (PFC), which is an oxygen carrier, was added to the fermentation medium. The presence of 50% (v/v) PFC in the fermentation medium resulted in a five-fold increase in the final antibiotic concentration. As a result of the importance of drop size distribution and the liquid-liquid interfacial area in such multiphase systems, the effects of dispersed phase (PFC phase) volume fraction on size distribution and on interfacial area were investigated. The results showed that the size distribution was positively skewed and that the liquid-liquid interfacial area increased with increasing PFC concentration. The liquid-liquid interfacial area was proportional to PFC concentration to the power 1.53.
Keywords: Bacteria (microorganisms); Streptomyces coelicolor; actinorhodine; antibiotic agent; fluorocarbon; aqueous solution; article; bacterial metabolism; bioreactor; dispersion; drug manufacture; fermentation; gas; liquid; oxygen consumption; physical phase; streptomyces coelicolor